Going fully digital: utopia or reality? - FRAGGETTA, F.; PANTANOWITZ, L. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
Digital pathology in the last decade has largely centered around whole slide imaging (WSI). Since virtual microscopy was first introduced around 20 years ago 1, the field of digital pathology has rapidly evolved as this technology advanced (e.g. faster scan times, z-stacking), novel applications emerged (e.g. teleconsultation, image analysis), users slowly began to adopt these tools, clinical guidelines were accordingly developed (e.g. CAP recommendations for WSI validation) 2, and regulatory approval for primary diagnostic use was obtained 3. Leveraging technology to better understand disease is not new to the practice of pathology. Even centuries ago Virchow markedly advanced our field when he enthusiastically used a microscope to study histopathology.